Effects of low voltage electrical stimulation during bleeding and hot boning on beef loin eye and top round muscles - Axe, J.B.; Hunt, Melvin C.; Kropf, Donald H.; Gray, D.G.; Kastner, Curtis L.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Our study evaluated the effects of low voltage electrical stimulation (ES) during bleeding and hot boning at 1 hr postmortem on loin eye (LE) and top round (TR) muscles. Possibly because of relatively slow initial chilling rate used in our study, hot-boned (HB) muscles, even without ES, were comparable to conventionally chilled and boned counterparts. In fact, coupling ES with HB proved less desirable than HB only.
Keywords: Beef; Electrical stimulation; Hot boning; Loin eye; Top round